Toward eternity : a novel - Hur, Anton (Harper Via, an imprint of HarperCollinsPublishers, 2024)
Exploring the nature of intelligence and the unexpected consequences of progress, the meaning of personhood and life, and what we really have to fear from technology and the future, Toward Eternity is a gorgeous, thought-provoking novel that challenges the notion of what makes us human--and how love survives even the end of that humanity.